MXene in core–shell structures: research progress and future prospects. Issue 27 (29th June 2022) - Lamiel, Charmaine; Hussain, Iftikhar; Ogunsakin, Olakunle Richard; Zhang, Kaili
Abstract : MXene is an emerging two-dimensional (2D) material whose properties have been well-evaluated to cater to a wide range of applications. Abstract : MXene is an emerging two-dimensional (2D) material whose properties have been well-evaluated to cater to a wide range of applications. However, there are challenges in using MXenes that may impede their further use, such as aggregation, long shelf-life stability, oxidation, thermal and mechanical properties, etc. Thus, material developments with MXenes have shown great promise in solving these limitations. In this review, the challenges and research progress in the material development of MXenes towards core–shell structures and their applications are addressed. Particularly, the preparation techniques and mechanisms involving the successful attachment of MXenes as a core or shell are evaluated and discussed, along with the discussion of the challenges and solutions that arise from using MXenes. Additionally, key findings, evaluations, and applications of the MXene core–shell in energy storage and conversion are studied and assessed. The review ends with the future direction of utilizing and functionalizing MXenes in core–shell structures in expanding their development toward hybrid core–shell structures for prospective applications.